Prospection et peche de la crevette profonde Pandalus borealis au large des cotes de Terre-Neuve et de Nouvelle-Ecosse. - Fontaine, Bernard; L'Herrou, Roger; Decamps, Philippe; Paturel, Bernard (ISTPM, 1972)
To assess the potential fishery for Pandalus borealis, the R/V `CRYOS' made cruises, in 1970 off SW Newfoundland and in 1971 off Nova Scotia. The trenches where Pandalus is found and the 3 types of trawl (large mouth, balloon and flat) are described. Details of size of catches and of individuals, and also of fish species caught are given. Prawn stocks in these grounds seem to match those of grounds already being exploited. Significant fish catches may also be expected (e.g. skate, herring and cod). Canadian type trawlers of ~ 65 ft would be suitable to exploit this fishery.